Crossover of the hypothalamic pituitary–adrenal/interrenal, –thyroid, and –gonadal axes in testicular development - Castañeda Cortes, Diana Carolina (2014)
Besides the well-known function of thyroid hormones (THs) for regulating metabolism, ithas recently been discovered that THs are also involved in testicular development in mam-malian and non-mammalian species. THs, in combination with follicle stimulating hormone,lead to androgen synthesis inDanio rerio, which results in the onset of spermatogen-esis in the testis, potentially relating the hypothalamic–pituitary–thyroid (HPT) gland tothe hypothalamic–pituitary–gonadal (HPG) axes. Furthermore, studies in non-mammalianspecies have suggested that by stimulating the thyroid-stimulating hormone (TSH), THscan be induced by corticotropin-releasing hormone. This suggests that the hypothalamic–pituitary–adrenal/interrenal gland (HPA) axis might influence the HPT axis. Additionally, itwas shown that hormones pertaining to both HPT and HPA could also influence the HPGendocrine axis. For example, high levels of androgens were observed in the testis inOdon-thestes bonariensisduring a period of stress-induced sex-determination, which suggeststhat stress hormones influence the gonadal fate toward masculinization. Thus, this reviewhighlights the hormonal interactions observed between the HPT, HPA, and HPG axes usinga comparative approach in order to better understand how these endocrine systems couldinteract with each other to influence the development of testes.